2008
DOI: 10.1002/cjce.20062
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the solid hold‐up distribution in a fluidized bed of nanoparticles using radioactive densitometry and fibre optics

Abstract: An experimental study was conducted to assess the solid hold-up distribution in a fluidized bed of zirconia and aluminum nanoparticles. For this purpose, two different techniques, radioactive densitometry and fibre optic measurement, were used. The results showed that while the fluidization of these nanoparticles occurs in the agglomeration state, it performs homogeneously in terms of phase concentration. This matter is important especially when a polymerization reaction should take place uniformly on the surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 47 publications
(88 reference statements)
1
18
0
Order By: Relevance
“…These results are consistent with the results obtained in our previous work 17. It was mentioned that the fluidization of zirconia and aluminum occurs in agglomerate state as shown in Figure 9.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…These results are consistent with the results obtained in our previous work 17. It was mentioned that the fluidization of zirconia and aluminum occurs in agglomerate state as shown in Figure 9.…”
Section: Resultssupporting
confidence: 93%
“…According to the experiments,17 it was understood that by increasing the gas velocity, large agglomerates are broken to smaller ones due to higher drag force in higher gas velocities. Therefore, in the range of gas velocity where we did the fluidization experiments, the agglomerate size are smaller for higher gas velocity for a given particle type.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the marginal values of the Hausner ratio established by Gledart for the naturally cohesive powder cannot be essentially valid for all kinds of cohesive particulate beds. Similarly, Esmaeili et al [57] found that the Hausner ratio criterion introduced by Geldart cannot satisfactorily predict the Agglomerate Particulate Fluidization (APF) and Agglomerate Bubbling Fluidization (ABF) [2] behaviors of nano size cohesive particles.…”
Section: Measurement Of Hausner Ratiomentioning
confidence: 99%